2007
DOI: 10.1111/j.1750-3841.2007.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Antioxidant Effects of Cocoa Polyphenolic Extract on Free Radical Production and Cognitive Performances after Heat Exposure in Wistar Rats

Abstract: The preventive effects of ACTICOA powder (AP), a cocoa polyphenolic extract, on free radicals produced by leucocytes in rats after heat exposure (HE) and its protective effects on subsequent cognitive impairments were assessed. AP or vitamin E, the antioxidant reference, was orally administered to rats for 14 d before HE at 40 degrees C temperature during 2 h. The day after HE, free radical production by leucocytes in rats treated with AP or vitamin E was significantly reduced as compared to control. Unlike co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 29 publications
(34 reference statements)
1
23
0
2
Order By: Relevance
“…Major polyphenol compounds found in CPE are the epicatechin oligomer class, namely, procyanidins. It was reported that procyanidins comprise about 88% of ACTICOA powder, a cocoa polyphenolic extract [17]. Several recent studies have shown that CPE suppressed the proliferation of cancer cells and various biomarkers of tumorigenesis in both cell culture and animal models [4,5,18].…”
Section: Discussionmentioning
confidence: 99%
“…Major polyphenol compounds found in CPE are the epicatechin oligomer class, namely, procyanidins. It was reported that procyanidins comprise about 88% of ACTICOA powder, a cocoa polyphenolic extract [17]. Several recent studies have shown that CPE suppressed the proliferation of cancer cells and various biomarkers of tumorigenesis in both cell culture and animal models [4,5,18].…”
Section: Discussionmentioning
confidence: 99%
“…One study investigated the short-term effect of a cocoa polyphenolic extract, Acticoa powder, on free radicals produced by leucocytes after heat exposure and the protective effects on subsequent cognitive impairments. The authors concluded that 14-days oral administration of Acticoa powder could protect heat-exposed rats from cognitive impairment, and suggested that the improved cognitive outcomes may have been consequence of preservation of brain function as a result of reduced inflammatory aggression, or enhanced cerebral plasticity [27]. Another study addressed the effects of long-term (12 months) oral supplementation of the same polyphenolic extract, Acticoa powder, on cognitive functions in aged rats, showing improved cognitive performance in terms of spatial memory and short-and long-term learning.…”
Section: Discussionmentioning
confidence: 99%
“…These doses were selected from previous dose-response studies. 34,35 Treatments with AP or vehicle started 14 days prior to the induction of prostate hyperplasia and were given daily by oral gavage according to rat BW until the end of the study from Day 1 to Day 35. AP was dissolved in the vehicle, spring water, each day before administration to the animals.…”
Section: Treatmentsmentioning
confidence: 99%